Effect of hyperlipidemia on the outcome of in vitro fertilization in non-obese patients with polycystic ovary syndrome - Yang, Fang; Lu, Jin-Chun; Shen, Tao; Jin, Yi-Han; Liang, Yuan-Jiao (Frontiers in Endocrinology, 2023)
Introduction It is little known whether hyperlipidemia alone has adverse effects on the outcome of in vitro fertilization (IVF) in patients with polycystic ovarian syndrome (PCOS). Methods The PCOS patients with body mass index (BMI) < 30 kg/m2 were performed IVF or intracytoplasmic sperm injection treatment, including 208 fresh cycles and 127 frozen embryo transfer (FET) cycles. All the patients were divided into hyperlipidemia and control groups, and embryo quality and pregnancy outcomes between the two groups were compared. Results In the fresh cycles, total gonadotropin dosage in the control group was significantly lower than that in the hyperlipidemia group, and serum estradiol levels on trigger day were reversed (P < 0.05). The embryo fragment score was positively correlated with serum low-density lipoprotein level (r = 0.06, P < 0.05) and negatively with serum high-density lipoprotein (HDL) and lipoprotein A levels (r = -0.489 and -0.085, P < 0.01). Logistic regression analysis found that HDL was beneficial for clinical pregnancy (OR = 0.355, 95% CI: 0.135-0.938, P < 0.05). In the FET cycles, there were no differences in pulse index, systolic/diastolic ratio and serum estradiol and progesterone levels between the two groups, but resistance index in the hyperlipidemia group was significantly higher than that in the control group (P < 0.05). Conclusion Hyperlipidemia may increase the dosage of gonadotropin and have adverse effect on the embryo quality, endometrial receptivity, and clinical outcomes of lean PCOS patients. It is recommended that the non-obese patients with hyperlipidemia and PCOS perform lipid-lowering treatment before undergoing embryo transfer.